A New Subclass of k-Janowski Type Functions Associated with Ruscheweyh Derivative. (3rd May 2017) - Mahmood, Shahid; Malik, Sarfraz Nawaz; Mustafa, Saima; Riaz, S. M. Jawwad
Abstract : We introduce and investigate a new subclass V D k A, B, b, δ of analytic functions using Ruscheweyh derivative. We derive the coefficient inequalities and other interesting properties and characteristics for functions belonging to the general class, which we have introduced and studied in this article. We also observe that this class is preserved under the Bernardi integral transform.